Pembuatan Media Iklan Video Menggunakan Adobe Premiere Pro Untuk Promosi di Instagram Toko Kopi Ong Malang - Jani Pinta Ardharisma; Maskur; Joni Dwi Pribadi (CV. ITTC INDONESIA, 2024)
In the face of increasingly tough business competition, companies need to utilize social media, especially Instagram as an effective promotional platform through videos. This study aimed to create an advertising video as a promotional medium and measure the effectiveness of advertising using the Direct Rating Method (DRM). The type of research used was action research (Action Research). This research used interviews, documentation, observation and questionnaires. The results of the analysis showed that the advertising video for Toko Kopi Ong Malang is included in the effective category, with the results obtained in the attention dimension of 14.0, the understanding dimension of 13.6, the cognitive dimension of 14.8, the affective dimension of 14.4 and the attitude dimension of 14.8, for a total DRM of 71.6. From the results of this study, it can be concluded that video advertising media using Adobe Premiere Pro for promotion on Instagram Toko Kopi Ong Malang is effective.